Therapeutic Role of Mesenchymal Stem Cell-Derived Extracellular Vesicles in Female Reproductive Diseases - Liao, Zhiqi; Liu, Chang; Wang, Lan; Sui, Cong; Zhang, Hanwang (Frontiers in Endocrinology, 2021)
Reproductive disorders, including intrauterine adhesion (IUA), premature ovarian insufficiency (POI), and polycystic ovary syndrome (PCOS), are great threats to female reproduction. Recently, mesenchymal stem cells derived - extracellular vesicles (MSC-EVs) have presented their potentials to cure these diseases, not only for the propensity ability they stemmed from the parent cells, but also for the higher biology stability and lower immunogenicity, compared to MSCs. EVs are lipid bilayer complexes, functional as mediators by transferring multiple molecules to recipient cells, such as proteins, microRNAs, lipids, and cytokines. EVs appeared to have a therapeutic effect on the female reproductive disorder, such as repairing injured endometrium, suppressing fibrosis of endometrium, regulating immunity and anti-inflammatory, and repressing apoptosis of granulosa cells (GCs) in ovaries. Although the underlying mechanisms of MSC-EVs have reached a consensus, several theories have been proposed, including promoting angiogenesis, regulating immunity, and reducing oxidate stress levels. In the current study, we summarized the current knowledge of functions of MSC-EVs on IUA, POI, and PCOS. Given the great potentials of MSC-EVs on reproductive health, the critical issues discussed will guide new insights in this rapidly expanding field.